Parity in Architectural Spaces: a novel Design Methodology in conceiving a Contemporary Art Museum in Frankfurt am Main - Lacherre Martínez, Enrique Florentino (2007)
Develops the design of a new contemporary art museum, through the innovation of a new architectural design methodology aided by new computational techniques. Based on the structural capacity and geometric organization in the textile units, we speculate about a new way of conceiving spatiality and geometry helped by new computational techniques. Geometric units are digitally reproduced and a series of parameters from the architectural program are formulated. These performative mechanisms or models generate complex geometry based on the spatial needs of the building. The collection of results is analyzed and classified to generate geometry and architectural spatiality capable of containing a specific activity and area of the museum. The project conceptualizes the mathematical and inverse parity effect for the planning of the new contemporary art museum in the city of Frankfurt am Main.